A semiotic perspective on webconferencing-supported language teaching. Issue 1 (27th November 2015) - Guichon, Nicolas; Wigham, Ciara R.
Abstract: In webconferencing-supported teaching, the webcam mediates and organizes the pedagogical interaction. Previous research has provided a mixed picture of the use of the webcam: while it is seen as a useful medium to contribute to the personalization of the interlocutors' relationship, help regulate interaction and facilitate learner comprehension and involvement, the limited access to visual cues provided by the webcam is felt to be useless or even disruptive. This study examines the meaning-making potential of the webcam in pedagogical interactions from a semiotic perspective by exploring how trainee teachers use the affordances of the webcam to produce non-verbal cues that may be useful for mutual comprehension. The research context is a telecollaborative project where trainee teachers of French as a foreign language (FFL) met for online sessions in French with undergraduate Business students at an Irish university. Using multimodal transcriptions of the interaction data from these sessions, screen shot data, and students' post-course interviews, it was found, firstly, that while a head and shoulders framing shot was favoured by the trainee teachers, there does not appear to be an optimal framing choice for desktop videoconferencing among the three framing types identified. Secondly, there was a loss between the number of gestures performed by the trainee teachers and those that were visible for the students. Thirdly, when trainee teachers were able to coordinate the audio and kinesic modalities, communicative gestures that were framed, and held long enough to be perceived by the learners, were more likely to be valuable for mutual comprehension. The study highlights the need for trainee teachers to develop critical semiotic awareness to gain a better perception of the image they project of themselves in order to actualise the potential of the webcam and add more relief to their online teacher presence.